INFLUÊNCIA DAS VIVÊNCIAS ACADÊMICAS E DA AUTOEFICÁCIA NA ADAPTAÇÃO, RENDIMENTO E EVASÃO DE ESTUDANTES NOS CURSOS DE ENGENHARIA DE UMA INSTITUIÇÃO PRIVADA - Matta, Cristiane Maria Barra da (2019)
The impact of early academic life can affect self-efficacy and make it difficult college adjustment. The present study evaluated the influence of self-efficacy and academic experiences in the prediction of school performance and dropout. The data was collected from Sociodemographic Data, Academic Experience Questionnaire - reduced version (QVA-r) and the Self-efficacy Scale in Higher Education (AEFS). Entrance exam, school performance and dropout were provided by the institution in which the study was developed. Data were analyzed using descriptive and inferential statistics. A total of 407 mostly male freshmen from a private engineering school, with the average age of 18.5 years old participated in the study. The academic adjustment was favored not only by the satisfaction with the course, the institution and the positive interpersonal relationships, but also by the high self-efficacy in the social interaction. However, confidence in the ability to learn and demonstrate it, self-regulate actions and proactivity was somewhat reduced compared to self-efficacy in social interaction and academic management. The proposed model predicted 60% of variable criteria. The positive contributions were previous education, study habits, feelings toward the chosen course and career, academic self-efficacy and academic management. In addition to these factors, the academic success of the students could be attributed to the quality of the transition of the developmental period and the educational policies of the institution. Activities that foster “belief in self-efficacy,” studying habits and time management, and physical and psychological well-being, emotional balance, optimism and self-confidence were suggested. Deficient education on high school was a significant predictor of evasion, representing between 38% and 50%. Socioeconomic, vocational and interpersonal factors are clear determinants of dropout. The results were discussed based on literature.